Beyond a single conceptual caving model: monitoring evidence for multiple cave propagation mechanisms - Smit, G.; Ayotte, L.; Steffen, S.; Allen, S. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Conceptual models of cave propagation, including the Duplancic framework and fracture banding, are commonly applied in practice as if they represent a single, generalised failure process. However, increasingly detailed monitoring data from operating cave mines indicate cave propagation patterns that are not always consistent with the assumptions of any single existing model. This paper reviews principal cave propagation concepts described in the literature and presents selected tilt monitoring datasets from two operating cave mines that were originally implemented to track cave back location. During analysis, tilt changes were observed well ahead of the interpreted cave back, interpreted as spatially localised zones of elevated rock mass response separated by intervals of comparatively limited disturbance. Cave advance appears to occur in a non‑continuous, stepwise manner towards these zones. While such behaviour may be qualitatively consistent with fracture banding concepts or driven by geological features, the available datasets are incomplete and lack corroborating measurements, preventing definitive identification of the governing failure mechanism. The observations, however, are clearly inconsistent with the assumptions of a specific cave propagation concept, but more likely a combination of concepts. This paper therefore presents an intermediate assessment intended to document these behaviours, define current interpretive limitations, and outline lessons learned to guide future monitoring and investigation, rather than to validate any specific cave propagation model.